Formation mechanism of barium titanate single crystalline microplates based on topochemical transformation using bismuth-based precursors. Issue 4 (15th February 2021) - Jin, Li; Huang, Yunyao; Zhang, Leiyang; Qiao, Jun; He, Zhanbing; Jing, Ruiyi; Hu, Qingyuan; Du, Hongliang; Zhang, Lin; Chang, Yunfei; Wei, Xiaoyong; Yan, Yan
Abstract: Owing to their importance in applications related to textured ceramics engineering, two-dimensional perovskite single-crystal microplates are highly desirable. In this work, (001)-oriented perovskite-structured BaTiO3 (BT) single-crystal microplatelets were fabricated from an Aurivillius-structured BaBi4 Ti4 O15 precursor via topochemical transformation. XRD, SEM, DTA, and TEM characterizations were performed to investigate the crystallization behavior and morphology evolution of the product at different reaction stages, with a focus on the formation mechanism of BT single crystalline microplatelets. Our results indicate that secondary recrystallization repaired the significant micro-structural/crystalline damage that was caused, thereby preserving the single-crystal structure during structural conversion. The subsequent epitaxial growth and replenishment through Ostwald ripening resulted in more regular shapes and narrower distributions of BT microplatelets. This study not only suggests suitable BT template candidates for the application of textured ceramics, but also provides new insights into a simple topochemical transformation strategy for manufacturing two-dimensional perovskite microcrystals.